The Relationship between Employee Silence and Organizational Commitment in a Private Healthcare Company - Deniz, Nevin; Noyan, Aral; Ertosun, Oznur Gulen (Elsevier Science Bv, 2013)
There is an increasing awareness about the silence in organizations and literature about the relation between commitment and employee silence has not consistent findings. In addition to these; affective commitment is supported as the most important commitment behaviour that affects the performance of employees. Because of these literature feedbacks this study aimed to research the relationship between employee silence and affective commitment. This study adds to the body of knowledge about the relationship between the concepts and in the light of related hypothesis, significant and negative relationship between affective commitment and one of employee silence dimension (defensive silence) has been supported by empirical analysis.
9th International Strategic Management Conference -- JUN 27-29, 2013 -- Riga, LATVIA
Keywords: Organizational silence; employee silence; organizational commitment; affective commitment